Mass superinflation in the Reissner-Nordström black hole - Nihar Ranjan Ghosh; Malay K. Nandy (Nuclear Physics B, 2024)
Ever since Penrose and Simpson's prediction contradicted Novikov's idea that an infalling person would emerge into an asymptotically flat universe, there have been a continued interest in predicting the nature of singularity at the inner horizon of a Reissner-Nordström black hole. This prediction was first confirmed by Poisson and Israel using cross-stream of massless particles, leading to the phenomenon coined as mass inflation. On the other hand, Ori obtained a weaker singularity using a null shell of radiation. Thus it is important to capture the nature of singularity at the inner horizon. We therefore consider in this work a massive scalar field coupled to the Reissner-Nordström spacetime. The ensuing field equations lead to a coupled set of nonlinear dynamical equations. For definiteness, we analytically solve these equations employing the Adomian decomposition method. This facilitates in obtaining a closed form solution that exhibits an unbounded double-exponential growth in the mass function, giving rise to a novel phenomenon coined herein as mass superinflation. The scalar field is also found to undergo a very strong blueshift at the inner horizon.